Reasons for Selecting a Dual Bachelor's Degree in Economics and the Results of the Training Form in Regards to Competences: Visszajelzések a duális képzésről - Liber, Evelin Fatime (Acta Carolus Robertus, 2024)
Nowadays, the labor market presents new challenges to the higher education system. This thesis is intended to highlight a part of the research presented at the TDK conference to be held in 2022 and a part of the thesis defended at the final exam to be held in January 2023. The topic of the research is the results of the dual training, the results formulated by students who graduated from or are currently participating in economics bachelor's programs. The present study is a brief summary of the answers goven to two research questions. The purpose of the first is the reasons for the students' selection of dual training, the second is to collect the competencies developed during the training. A total of 35 current or already graduated students participated in the research. The study highlights the results obtained for three of the 12-question interviews. Based on student feedback, the main motivations for selecting dual education are gaining experience, faster and broader development of competencies, and increasing the income that can be earned during the university years. The competencies developed during the training and highlighted by most students are communication skills, professional competencies, and the ability to work in a team.
Keywords: higher education; dual training; bachelor's degree in economics; competences